Adat, People Power and Religious Values: Sources of Social Resilience from the Early to Middle 19th Century in Bali - I Ketut Ardhana; I Nyoman Wardi (Pusat Kajian Bali Universitas Udayana, 2022)
Adat and religious values played a significant role in the rise of social movements and people power during the Dutch colonial era which is evident in the dynamics of Bali in particular. For centuries, adat customary traditions had been deeply rooted in Balinese communities and strongly contributed to civilization and culture. However, certain factors, such as social, economic and political disturbances have threatened the stability of Balinese communities and culture. From the local perspective of Bali, this posed a threat against the sovereignty of the kingdom of Bali, was still recognized as an autonomous territory. In light of the above issues, this article used an interdisciplinary approach to historiography in analyzing oral history and textual archives. It is hoped to offer a better understanding of how historical Balinese adat and religious values fostered an increase in social resilience and people power when faced with externally generated disturbances.